2013
DOI: 10.1055/s-0033-1350828
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Ultrasound in the Treatment of Breast Cancer

Abstract: !Purpose: The aim of this study was to investigate the value of intraoperative ultrasound in breastconserving operations and to compare it with standard procedures. Methods: For this purpose 307 women with palpable breast cancers and 116 patients with nonpalpable breast cancers were compared retrospectively. In the group with palpable breast cancers 177 patients were treated by US-guided operations and 130 patients underwent palpationguided breast-conserving operations. As primary outcomes, the resection margi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Surgical resection remains the primary treatment for breast cancer, though without intraoperative guidance, almost one-quarter of patients undergo additional excision surgery due to positive margins (2). Intraoperative ultrasound for intraoperative guidance has been shown to reduce the rate of positive margins, thereby improving morbidity and mortality, decreasing resected surgical volumes and improving patient satisfaction with improved post-operative cosmetic appearance (38,39). However, ultrasound as a screening methodology has limited positive predictive value and cannot differentiate between benign and malignant lesions (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection remains the primary treatment for breast cancer, though without intraoperative guidance, almost one-quarter of patients undergo additional excision surgery due to positive margins (2). Intraoperative ultrasound for intraoperative guidance has been shown to reduce the rate of positive margins, thereby improving morbidity and mortality, decreasing resected surgical volumes and improving patient satisfaction with improved post-operative cosmetic appearance (38,39). However, ultrasound as a screening methodology has limited positive predictive value and cannot differentiate between benign and malignant lesions (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, intraoperative monitoring of the removed tissue by ultrasound instead of mammography could probably confirm adequate resection by locating the clip, which would increase the efficiency of the workflow and decrease radiology costs [11]. This could result in a decrease in surgery time, re-excision rates, resection volume, and overall cost [17][18][19]. While we did not compare the Tumark Vision clip to other commercially available clips, comparisons between clips have shown that newer self-expanding clips show a lower displacement rate compared with bare metal clips [20].…”
Section: Discussionmentioning
confidence: 99%
“…The technical achievements permitted the extension of IOUS in many fields of surgery: nervous system, cardiovascular system, endocrine gland, breast [6][7][8][9]. The benefits of IOUS has expended beyond diagnostics; the ultrasound image represents nowadays, a guidance for surgical maneuvers.…”
Section: Introductionmentioning
confidence: 99%